Bisalbuminemia: Diagnostic Pearls from A Case Series - Sneha Wadalkar; Shalini Maksane; Kavita More; Kshama Pimpalgoankar (National Journal of Medical Research)
Bisalbuminemia (alloalbuminemia) is a rare, often incidental electrophoretic abnormality characterized by the presence of two distinct albumin bands, resulting from albumin variants with differing electrophoretic mobilities. Between the year 2020 and 2022, three cases of Bisalbuminemia were identified through serum protein electrophoresis (SPE) in varying clinical contexts. These included one confirmed case of multiple myeloma, one suspected case of monoclonal gammopathy, and one asymptomatic individual in whom Bisalbuminemia was detected incidentally during routine screening. Although typically benign, Bisalbuminemia may coexist with plasma cell disorders and has the potential to mimic or obscure monoclonal bands on electrophoretic analysis, leading to diagnostic challenges. Accurate recognition and interpretation of this phenomenon are essential to prevent misdiagnosis or overlooked pathology. These cases highlight the importance of correlating electrophoretic findings with clinical and laboratory data. While Bisalbuminemia itself is usually asymptomatic and benign, its presence in the context of monoclonal gammopathies raises questions about potential clinical significance. Further research is warranted to investigate whether this anomaly has any functional or pathological implications in plasma cell dyscrasias. Awareness of Bisalbuminemia among clinicians and laboratory professionals can improve diagnostic accuracy and patient management in cases involving abnormal protein electrophoresis.